INTEGRATION OF GENDER EQUALITY AND SOCIAL INCLUSION (GESI) IN PARTICIPATORY PLANNING OF INFORMAL SETTLEMENTS: CASE STUDY OF TAMMUA URBAN VILLAGE, MAKASSAR - Andi Annisa Amalia; Citra Amalia Amal; Khilda Wildana Nur; Muhammad Aldi; Hamzah Hamid; Andi Adam Sawerigading; Muhammad Alfacmy Nurawal (Center for Scientific Publication, 2025)
RT 002 RW 004, Tammua Urban Village in Makassar City is an informal settlement with the highest level of vulnerability, characterized by high population density, irregular building structures, limited access to clean water, sanitation, and open spaces, as well as overlapping land uses among residential, industrial, and transportation areas. This study evaluates the integration of Gender Equality and Social Inclusion (GESI) principles in the participatory planning of informal settlements through a review of the Tammua Community Settlement Environmental Planning (RPLP) document. Spatial analysis was used to identify correlations between housing density, building feasibility, and access to basic infrastructure with the distribution of vulnerable groups through a GESI lens. Results indicate that the RPLP has attempted to thematically mainstream GESI using the Analysis, Participation, Control, and Benefit (APKM) framework. Thematic maps reveal spatial correlations between housing density, building feasibility, and infrastructure access with the distribution of vulnerable groups. However, participation of vulnerable communities remains limited; housing density reaches 711.11 units/ha, 82 households lack access to clean water, and drainage infrastructure is damaged over 7,359 meters. Due to inadequate sanitation, most residents still rely on dug wells for bathing, washing, and defecation. The study concludes that the integration of GESI in participatory planning in Tammua needs improvement, particularly in substantially involving vulnerable groups, creating adaptive spatial designs, and equitably distributing infrastructure to realize adequate, resilient, and equitable urban housing conditions.